SWOT Analysis in Smart City Project Management: Adaptation Strategy to the Industrial Revolution 5.0 - Badirun Basir; Ida Ayu Trisna Wijayanthi (Maneggio, 2025)
The Industrial Revolution 5.0 brings a paradigm shift towards harmonious collaboration between humans and intelligent machines, demanding a human-centric approach in Smart City development. Smart City projects in this era must be adaptive, not only integrating technologies such as IoT and AI, but also considering social dynamics, culture, and digital ethics. Key challenges include the digital divide, social resistance, and the need for more flexible and collaborative project management. This study aims to analyze the use of SWOT as an adaptive strategy tool in dealing with this complexity. The method used is a qualitative-descriptive approach through case studies in several major cities in Indonesia, with data collection techniques in the form of interviews, documentation studies, and observations. SWOT is developed from being an evaluative tool into a dynamic strategy framework that takes into account technological, social, cultural, and sustainability factors. The findings show that the integration of SWOT with additional analysis such as PESTLE and Balanced Scorecard strengthens the adaptive power of Smart City management, allowing for the formulation of strategies that are more responsive to exponential change. This study recommends updating the SWOT framework to accommodate the values of the Industrial Revolution 5.0, thereby supporting the development of more inclusive, humanistic, and sustainable smart cities